RIFM fragrance ingredient safety assessment, 1, 2, 3, 3a, 4, 5, 6, 8a-octahydro-4, 8-dimethyl-2-(1-methylethylidene)-6-azulenol, CAS Registry Number 89-88-3. (June 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: 1, 2, 3, 3a, 4, 5, 6, 8a-Octahydro-4, 8-dimethyl-2-(1-methylethylidene)-6-azulenol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.